The FINANCIAL BEHAVIOR WITH A CASE-BASED APPROACH AND TECHNOLOGY ADAPTATION AT KBTK STAR KIDS: FINANCIAL BEHAVIOR WITH A CASE-BASED APPROACH AND TECHNOLOGY ADAPTATION AT KBTK STAR KIDS - Lestari, Elly Lestari; Setyawati, Yuni Setyawati (PENANOMICS: International Journal of Economics, 2024)
The study reveals that KBTK Star Kids has successfully digitized its financial transactions using Microsoft Excel for financial reporting and Android-based accounting apps installed on mobile devices. Financial records are carefully separated between personal and business accounts to streamline financial management. Additionally, the adaptation of advanced technology at KBTK Star Kids aims to enhance early childhood education by providing interactive, productive, and enjoyable learning experiences. Information and Communication Technology (ICT), combining hardware and software, is increasingly influential in education. KBTK Star Kids' effective use of ICT is crucial for its global competitiveness and performance improvement, reflecting its ability to modernize and integrate technology in both financial management and educational practices.